In-situ preparation of SiC reinforced Si3N4 ceramics aerogels by foam-gelcasting method - Han, Lei; Li, Xiaojian; Li, Faliang; Zhang, Haijun; Liu, Xueyin; Li, Guangqiang; Jia, Quanli; Zhang, Shaowei (Ceramics international, 2022)
High strength SiC reinforced Si3N4 ceramics aerogels (SCSNCAs) were fabricated via foam-gelcasting and subsequent catalytic reaction, utilizing industrial Si and melamine as raw materials, a small amount of incidental Fe impurities in Si powder as the catalyst and cetyltrimethylammonium bromide (CTAB, the amount of 0.075 wt%) as foaming agent. The effects of solid loading level and reaction temperature on phase composition, microstructure and mechanical properties of the as-prepared SCSNCAs were examined. The aerogels prepared at 1423 K using a slurry of solid loading level of 30 wt% (Si:melamine = 3:1, mass ratio) had porosity of 91.9%, having compressive and specific strength of 0.8 MPa and 3.8 MPa·cm3·g−1 exhibited the lowest thermal conductivity of 0.066 W/(m·K) at 473 K. Compared with the control sample (without melamine, i.e., Si3N4 aerogels without the formation of SiC), the specific strength of the SCSNCAs increased by about 10%, which was attributed to the additional reinforcement from SiC whiskers formed in the Si3N4 matrix of the aerogels.